2010
DOI: 10.1007/s11136-010-9614-8
|View full text |Cite
|
Sign up to set email alerts
|

Restless legs syndrome and its relationship with anxiety, depression, and quality of life in cancer patients undergoing chemotherapy

Abstract: Introduction Extended half-life factor products have reduced annualized bleeding rates in hemophilia patients. The impact of extended half-life versus conventional factor products on hemophilia caregiver burden has not been investigated. This study aimed to evaluate caregiver burden in extended half-life versus conventional factor products for hemophilia A and B. Methods This cross-sectional web-based study of caregivers of people with hemophilia A or B was recruited from a panel research company and by word o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 29 publications
6
26
0
Order By: Relevance
“…In this our results are in line with those reported by others [24,46], who found that quality of life was substantially affected in patients suffering from RLS compared to indices from a general population.…”
Section: Discussionsupporting
confidence: 93%
“…In this our results are in line with those reported by others [24,46], who found that quality of life was substantially affected in patients suffering from RLS compared to indices from a general population.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, a high frequency of RLS was found in ACP 34. The exact aetiology is not clear, but use of antidepressant medications, especially the, caffeine use and anaemia (iron deficiency), are common contributors to RLS and are frequently seen in patients with advanced cancer 35.…”
Section: Discussionmentioning
confidence: 64%
“…Cancer pa- tients afflicted by RLS had significantly higher levels of anxiety and depression, and poorer quality of life. 49 In Koreans, having RLS was associated with depression and anxiety disorders 50 ; in uremic patients, increased anxiety levels was an independent predictor of RLS. 51 We are unable to explain from our data why only men, primarily younger men, had lower RLS prevalence than younger women, as would be suggested by previously reported higher prevalence of RLS in women.…”
Section: Acculturation and Prevalence Of Rlsmentioning
confidence: 95%